2017
DOI: 10.1088/1741-2552/aa5f27
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond UV lasers stimulate transient Ca2+elevations in human hNT astrocytes

Abstract: We propose that nanosecond laser stimulation provides a valuable tool for enabling the study of Ca dynamics in human astrocytes at both a single cell and network level. Compared to previously developed techniques nanosecond laser stimulation has the advantage of not requiring loading of photo-caged or -sensitising agents, is non-contact, enables stimulation with a high spatiotemporal resolution and is comparatively cost effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…hNTs have already been used for cell transplantation in stroke therapy [14], demonstrating functional astrocyte-neuron lactate shuttle [15] and developing a human neuronal cell model for human immunodeficiency Virus (HIV)-infected macrophage-induced neurotoxicity [16]. Our group has extensive experience of these cells, patterning both hNT neurons and astrocytes on parylene-C/SiO 2 substrates [7,9,[17][18][19] and demonstrating that hNT astrocytes elevate transient Ca 2+ response stimulated by nanosecond UV lasers [20]. In addition, hNT neurons and hNT astrocytes do not raise ethical concerns as they come from an immortalised stem cell line [21].…”
Section: Ntera2 Cell Line Derived Astrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…hNTs have already been used for cell transplantation in stroke therapy [14], demonstrating functional astrocyte-neuron lactate shuttle [15] and developing a human neuronal cell model for human immunodeficiency Virus (HIV)-infected macrophage-induced neurotoxicity [16]. Our group has extensive experience of these cells, patterning both hNT neurons and astrocytes on parylene-C/SiO 2 substrates [7,9,[17][18][19] and demonstrating that hNT astrocytes elevate transient Ca 2+ response stimulated by nanosecond UV lasers [20]. In addition, hNT neurons and hNT astrocytes do not raise ethical concerns as they come from an immortalised stem cell line [21].…”
Section: Ntera2 Cell Line Derived Astrocytesmentioning
confidence: 99%
“…A 200 nm SiO 2 layer, verified with a Nanometrics NanoSpec/ AFT Microarea gauge, was produced on silicon wafers under a flow of 1.88 and 1.25 sccm of H 2 and O 2 , respectively, in a furnace at 950 °C for 40 min. Then, a 100 nm thick layer of parylene-C was deposited onto oxidised wafers via a speciality coating systems at room temperature [20].…”
Section: Manufacture Of Parylene-c/sio 2 Substratesmentioning
confidence: 99%
“…Our group has previously demonstrated that nanosecond UV laser stimulation is a reliable and repeatable method to induce Ca 2+ transients in human NTERA2/D1 (hNT) astrocytes [45] in vitro and in small networks of hNT astrocytes [46,47]. Our aim in this article is to expand on this work to generate Ca 2+ elevations in three patient-derived GBM cell-lines.…”
Section: Introductionmentioning
confidence: 99%
“…Our group is involved in understanding the calcium communication in networks of human hNT astrocytes (Raos et al, 2013(Raos et al, , 2017Jordan et al, 2016;Li et al, 2019). Astrocytes were commonly thought of as perfunctory cells, however, recent evidence has demonstrated that they possess far more functionality and complexity than was commonly thought.…”
Section: Introductionmentioning
confidence: 99%